Role of vitamins A, C, D, E in cancer prevention and therapy: therapeutic potentials and mechanisms of action - Talib, Wamidh H.; Ahmed Jum’AH, Dima Abdulraheem; Attallah, Zeena Shamil; Jallad, Mohanned Sami; Al Kury, Lina T.; Hadi, Rawan Wamidh; Mahmod, Asma Ismail (Frontiers in Nutrition, 2024)
Cancer, a leading global cause of mortality, arises from intricate interactions between genetic and environmental factors, fueling uncontrolled cell growth. Amidst existing treatment limitations, vitamins have emerged as promising candidates for cancer prevention and treatment . This review focuses on Vitamins A, C, E, and D because of their protective activity against various types of cancer. They are essential as human metabolic coenzymes. Through a critical exploration of preclinical and clinical studies via PubMed and Google Scholar, the impact of these vitamins on cancer therapy was analyzed, unraveling their complicated mechanisms of action. Interestingly, vitamins impact immune function, antioxidant defense, inflammation, and epigenetic regulation, potentially enhancing outcomes by influencing cell behavior and countering stress and DNA damage. Encouraging clinical trial results have been observed; however, further well-controlled studies are imperative to validate their effectiveness, determine optimal dosages, and formulate comprehensive cancer prevention and treatment strategies.Personalized supplementation strategies, informed by medical expertise, are pivotal for optimal outcomes in both clinical and preclinical contexts. Nevertheless, conclusive evidence regarding the efficacy of vitamins in cancer prevention and treatment is still pending, urging further research and exploration in this compelling area of study.